2020
DOI: 10.1136/bmjoq-2020-000949
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned: using adverse incident reports to investigate the characteristics and causes of prescribing errors

Abstract: IntroductionPrescribing errors are a principal cause of preventable harm in healthcare. This study aims to establish a systematic approach to analysing prescribing-related adverse incident reports, in order to elucidate the characteristics and contributing factors of common prescribing errors and target multifaceted quality improvement initiatives.MethodsAll prescribing-related adverse incident reports submitted across one NHS board over 12 months were selected. Incidents involving commonly implicated drugs (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The present study did not find signals for commonly mentioned high‐risk medicines such as gentamicin, digoxin and methotrexate 26 . Gentamicin was previously found to be associated with MEs in a study on ME in children 17 and in a study on prescribing MEs in a general population 30 . This discrepancy may be explained by the differences in the investigated populations (adult, pediatric and general).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The present study did not find signals for commonly mentioned high‐risk medicines such as gentamicin, digoxin and methotrexate 26 . Gentamicin was previously found to be associated with MEs in a study on ME in children 17 and in a study on prescribing MEs in a general population 30 . This discrepancy may be explained by the differences in the investigated populations (adult, pediatric and general).…”
Section: Discussionmentioning
confidence: 95%
“…26 Gentamicin was previously found to be associated with MEs in a study on ME in children 17 and in a study on prescribing MEs in a general population. 30 This discrepancy may be explained by the differences in the investigated populations (adult, pediatric and general).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of the problems that can occur, in a study of 330 reports of adverse incidents related to prescriptions the drugs most commonly involved were insulin (10% of incidents), gentamicin (7%), co-amoxiclav (5%), and amoxicillin (5%). In 15 cases co-amoxiclav was given to people with penicillin allergy (4.5% of the total) 14. If you don’t know that co-amoxiclav contains amoxicillin, this is an error that you can easily make, with potentially fatal consequences.…”
Section: Mixtures and Co-namesmentioning
confidence: 99%
“…According to an investigation by Taiwan's Ministry of Health and Welfare, from 2014 to 2019, there were more than 20,000 adverse drug events (ADEs) every year. Some studies found that many serious medical errors-which cause or have the potential to cause damage or injury-are drug prescription or administration errors [1][2][3][4]. Different studies have used interventions to reduce these errors.…”
Section: Introductionmentioning
confidence: 99%